2004
DOI: 10.1042/bj20040592
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding, but not interaction with Bmal1, is responsible for DEC1-mediated transcription regulation of the circadian gene mPer1

Abstract: DEC1 (differentially expressed in chondrocytes 1) and DEC2 are E-box-binding transcription factors and exhibit a circadian expression pattern. Recently, both proteins were found to repress the Clock/Bmal1-activated E-box promoters (e.g. mPer1). Yeast two-hybrid assay detected interactions between Bmal1 and DECs. It was hypothesized that DEC-mediated repression on the mPer1 promoter is achieved by binding to E-box elements and interacting with Bmal1. In the present study, we report that E-box binding rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 41 publications
3
42
0
Order By: Relevance
“…Further characterization of Dec1 and Dec 2 demonstrated that these two genes underwent 24-h oscillations in the hypothalamic suprachiasmatic nucleus (SCN). Their gene products (proteins) were found to inhibit the transcriptional activity of the BMAL1/ CLOCK complex by direct binding to BMAL1 and competitive inhibition for the binding of the complex to E-box [95,113,114].…”
Section: Long Bone Growth Chondrocyte Proliferation and Differentiamentioning
confidence: 99%
“…Further characterization of Dec1 and Dec 2 demonstrated that these two genes underwent 24-h oscillations in the hypothalamic suprachiasmatic nucleus (SCN). Their gene products (proteins) were found to inhibit the transcriptional activity of the BMAL1/ CLOCK complex by direct binding to BMAL1 and competitive inhibition for the binding of the complex to E-box [95,113,114].…”
Section: Long Bone Growth Chondrocyte Proliferation and Differentiamentioning
confidence: 99%
“…Although DEC1 prevents neither C/EBPβ nor RXR from binding to its target gene, DEC1 prevents bHLH domain containing transactivators such as BMAL1, MyoD and SREBP-1c, from binding to their target DNA by either protein-protein interaction or by directly binding to their responsive elements containing an E-box (Azmi et al, 2004;Choi et al, 2008;Li et al, 2004). Recently, Gulbagci et al demonstrated that DEC2, isoform of DEC1, also interacts with C/EBPβ and increases the recruitment of histone methyltransferase G9a to the promoter of PPARγ2 (Gulbagci et al, 2009).…”
Section: Dec1 Is Recruited On the Promoter Of Pparγ2mentioning
confidence: 99%
“…STRA13 null mice, although surviving to adulthood, develop autoimmune diseases accompanied by accumulation of spontaneously activated T and B cells (Sun et al, 2001). Furthermore, these proteins are found to interact directly with clock protein BmalI and regulate the expression of biological clock regulator Per (Honma et al, 2002;Li et al, 2004).…”
Section: Introductionmentioning
confidence: 99%